2023
DOI: 10.1111/mec.16915
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal microbiota of Nearctic‐Neotropical migratory birds vary more over seasons and years than between host species

Abstract: Seasonal migration of Nearctic‐Neotropical passerine birds may have profound effects on the diversity and abundance of their host‐associated microbiota. Migratory birds experience seasonal change in environments and diets throughout the course of the annual cycle that, along with recurrent biological events such as reproduction, may significantly impact their microbiota. In this study, we characterize the intestinal microbiota of four closely related species of migratory Catharus thrushes at three time points … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 110 publications
0
1
0
Order By: Relevance
“…Between-habitat comparison of the gut microbial community in nine species of Darwin’s finches showed that lowland versus highland habitat variation was a primary determinant the microbiome composition (Loo et al 2019 ). Interspecific comparisons also indicated that local environmental conditions may be considered a crucial driver of the gut microbiota composition in birds and their importance may even exceed the effects of phylogenetic relationships (Hird et al 2014 , Grond et al 2019 , Skeen et al 2023 ). In agreement with this hypothesis, we observed a relatively good clustering of individual microbiome composition by the stopover site habitat (within species), and this clustering was more apparent that the clustering by species.…”
Section: Discussionmentioning
confidence: 99%
“…Between-habitat comparison of the gut microbial community in nine species of Darwin’s finches showed that lowland versus highland habitat variation was a primary determinant the microbiome composition (Loo et al 2019 ). Interspecific comparisons also indicated that local environmental conditions may be considered a crucial driver of the gut microbiota composition in birds and their importance may even exceed the effects of phylogenetic relationships (Hird et al 2014 , Grond et al 2019 , Skeen et al 2023 ). In agreement with this hypothesis, we observed a relatively good clustering of individual microbiome composition by the stopover site habitat (within species), and this clustering was more apparent that the clustering by species.…”
Section: Discussionmentioning
confidence: 99%
“…Seasonal variations in the gut microbiota have been reported in a variety of vertebrate lineages, including birds, reptiles, and mammals. Wild bird studies, such as those of hooded cranes, passerine birds, Catharus thrushes, and Sichuan partridges, have demonstrated that the seasonal modulation of the gut microbiota often corresponds to seasonal changes in diet [42,[48][49][50]. While research on homing pigeons given the same diet in the Netherlands suggests that temperature played a role in the seasonal variations in the composition of the gut bacterial community [11], this study presents the first evidence of seasonal effects on the gut bacterial community in captive wintering ducks in China.…”
Section: Seasonal Variation Effectmentioning
confidence: 99%
“…Migratory birds possess complex and diverse gut microbiomes due to their seasonal and extensive movements (Zhang et al., 2021 ). Recent studies have revealed the influence of migration and environmental factors on the interaction between diet and gut microbiota (Grond et al., 2014 ; Ryu et al., 2014 ; Skeen et al., 2023 ). Migratory birds face physiological challenges during long‐distance movements, including energy demands, environmental stress, and immunity, which result in weight loss and gastrointestinal atrophy (Buehler & Piersma, 2008 ; McWilliams & Karasov, 2001 ; Weber, 2009 ).…”
Section: Introductionmentioning
confidence: 99%